Socio-economic correlates and determinants of cashew productivity: An analysis of Dakshina Kannada district - Sajeev, M.V.; Saroj, P.L.; Lakshmisha, R. (Journal of Plantation Crops, 2014)
The study analyses the socio-economic correlates and determinants of cashew productivity in the Dakshina Kannada district of Karnataka state, as a prerequisite for developing and initiating effective extension interventions for combating low productivity and profitability from cashew cultivation. Results show that majority of the cashew farmers recorded medium to low productivity in cashew cultivation. Extension contact and participation were identified as significant correlates of cashew production and productivity along with level of education and primary occupation. Age of the farmer, primary occupation, years of experience in farming, cosmopoliteness, number of yielding cashew trees, yearly expenditure made in cashew farming and net income from cashew farming were identified as determinants of cashew productivity. The study suggests motivating farmers to take up cashew cultivation in high density mode, undertake cashew cultivation in better quality land with recommended management practices and proportionately increasing yearly expenditure for cashew farming in relation to net income from agriculture. The results clearly indicate that socio-personal and economic correlates and determinants along with policy environment have a larger contribution in explaining cashew productivity, while technology component alone cannot be expected to bring a positive impact.